'To Clapham's I go': a mid to late 18th-century Cambridge coffeehouse assemblage. (4th May 2017) - Cessford, Craig; Hall, Andy; Herring, Vicki; Newman, Richard
Abstract : SUMMARY: The recovery of a large closely dated assemblage that can be unambiguously associated with a mid to late 18th-century Cambridge coffeehouse provides the first opportunity for a detailed consideration of material associated with these significant institutions. A cellar located off All Saints' Passage in Cambridge, England, backfilled c . 1775–80, produced a substantial assemblage of over 500 objects; principally ceramics, but also including vessel glass, clay tobacco pipes, animal bone and other material. Marked items and assemblage composition allows this material to be unambiguously associated with Clapham's Coffeehouse, run by William and Jane Clapham c . 1746/48–79. Relatively few archaeological assemblages related to these important 18th-century socioeconomic institutions have been recovered and the material associated with Clapham's Coffeehouse possesses a distinctive 'signature', albeit one that is not necessarily generally applicable to other coffeehouses. There were a substantial number of ceramics associated with tea drinking. Coffee-drinking vessels were frequent but less common and there was relatively little evidence for chocolate drinking. A range of alcoholic drinks were also consumed and dining was common, with a particular emphasis on snacks, whilst smoking appears to have been uncommon. The assemblage is compared with other groups associated with coffeehouses, a series of groups from earlier inns in the vicinity and broadly contemporary domestic assemblages from Cambridge and inn groups from England. The archaeological evidence indicates that the materialities of coffeehouses were not significantly different to that of other establishments, such as inns, and challenges some currently held views of coffeehouses derived from documentary sources.